Platelet ultrastructural morphometry for diagnosis of partial delta-storage pool disease in patients with mild platelet dysfunction and/or thrombocytopenia of unknown origin. A study of 24 cases - Pujol-Moix, N; Hernandez, A; Escolar, G; Espanol, I; Martinez-Brotons, F; Mateo, J (Haematologica (Roma), 2000)
Departament d'Hematologia. Hospital de la Santa Creu i Sant Pau, Universitat Autonoma de Barcelona, Spain. npujol@hsp.santpau.es/npujolm@aehh.org. BACKGROUND AND OBJECTIVE: Exact diagnosis is sometimes difficult in patients presenting with a slight bleeding diathesis, prolonged bleeding times, non-specific aggregometric abnormalities, and/or mild thrombocytopenia. The objective of this study was to evaluate the use of platelet ultrastructural morphometry in detecting a partial d-storage pool disease in such patients. DESIGN AND METHODS: Platelets from 52 patients and 15 controls were fixed immediately in glutaraldehyde in White's saline without anticoagulant and processed for transmission electron microscopy. Using computer-assisted morphometry, the size and shape of the platelets were measured, as were the size and number per platelet of the dense- and a-granules. Ultrastructural morphology of the above and other intraplatelet structures was observed. RESULTS: Twenty-four cases were diagnosed as having a partial d-storage pool disease. Mean platelet area (2.28 microm(2)) and maximum diameter (2.58 microm) were significantly greater in patients than in control subjects (1.64 microm(2) and 2. 25 microm, respectively) but discoid shape was preserved. Mean dense-granule number was decreased, both per platelet and per microm(2) of platelet area (patients 0.22 and 0.09; controls 0.42 and 0.24). Seven patients also had a marked decrease in a-granules, resulting in a significantly lower mean number of granules per microm(2 )(patients 2.43; controls 3.15). Additionally, the patients' platelets had significant increases in both lipid droplets and surface-connected canalicular system. INTERPRETATION AND CONCLUSIONS: A partial dense-granule deficiency, sometimes associated with partial a-granule deficiency, should be borne in mind faced with patients who have a slight bleeding diathesis, non-specific platelet dysfunction tests and/or mild thrombocytopenia of unknown origin. Platelet ultrastructural morphometry is useful in diagnosing this condition.